2020
DOI: 10.1111/cob.12397
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in plasmin inhibitor and fibrinogen predict the improved fibrin clot lysis 6 months after obesity surgery

Abstract: Summary Prothrombotic and metabolic variables are decreased after obesity surgery, and fibrin clot lysis is increased. It is unknown how fibrinolytic variables are affected, and whether fibrinolytic and metabolic changes predict the enhanced clot lysis. Study aims were to determine fibrinolytic biomarkers before and 6 months after Roux‐en‐Y gastric bypass (RYGB) and to identify predictors of the RYGB‐induced increase in clot lysis. Women (n = 42) and men (n = 18) with obesity underwent RYGB, and factor XIII (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Notably, a further substudy by Pedersen et al. [ 21 ] specifically linked a reduction in PI and fibrinogen 6 months after bariatric surgery to improved lysis. Therefore, it is conceivable that lysis times did not change due to the unaltered fibrinogen (and potentially PI) concentration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, a further substudy by Pedersen et al. [ 21 ] specifically linked a reduction in PI and fibrinogen 6 months after bariatric surgery to improved lysis. Therefore, it is conceivable that lysis times did not change due to the unaltered fibrinogen (and potentially PI) concentration.…”
Section: Resultsmentioning
confidence: 99%
“…These studies showed that RYGB led to an improvement in clot lysis 6, 12, and 24 months after surgery [ 19 , 20 ]. A later substudy showed that the enhanced clot lysis 6 months after surgery was predicted by reductions in circulating fibrinogen and plasmin inhibitor (PI) [ 21 ]. It is noted, however, that the factors influencing fibrin clot structure and fibrinolysis are complex.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to improved asthma control, bariatric surgery corrects inflammatory cytokine and adipokine profiles. Circulating levels of leptin, TNF-α, IL-6 and C-reactive protein (CRP), an indirect inhibitor of tPA through augmentation of IL-1β and TNF-α, 94 significantly decrease 3-to-12 months following bariatric surgery, [95][96][97][98][99][100] with a concomitant increase seen in circulating adiponectin levels. [95][96][97] Serum levels of Type-2 cytokines IL-13 and chitinase-3-like protein 1 (YKL-40) are also shown to decrease following bariatric surgery.…”
Section: Bariatric Surgery Comorbid Obesity and Allergic Asthma And Coagulationmentioning
confidence: 99%
“…Bariatric surgery induces improvement in coagulation through normalized anti-coagulant and anti-fibrinolytic mediators. 22,[63][64][65][66]97,99,100,105 Batist et al reported increased systemic anti-thrombin III associated with bariatric surgery-stimulated weight loss. 63,105 Moreover, circulating PC/APC levels decreased 1 year following bariatric surgery due to reduced thrombomodulin and thrombin potential.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation